Reservas de surfe: uma análise jurídica da governança do espaço marinho-costeiro - Santos, Mauricio Duarte dos (2018)
Examining the governance of the sea, oceans and the coast is essential at both global and local levels. Considering the existing legal and institutional arrangements and peculiarities of the marine-coastal zones, it is pertinent to assess the potential of “surfing reserves” as a category of protected area (international level) and a territorial space to be protected (national level). The surfing reserves can be distinctly nominated as a policy instrument by the organised societies and/or governments to protect surf breaks, adjacent areas and surf culture. In this study on the surfing reserves, through exploratory research – bibliographical and documentary analysis – and, through a qualitative methodology, a descriptive analysis was carried out on the legislation and existing voluntary and cogent law models. The study highlights the historical transition to modern surfing and identifies the role of stakeholders’ participation from different countries in order to protect and use the marine-coastal spaces. It notes the advances in the creation of programs and laws and the need to adjust and create strategies for greater effectiveness. It presents propositions that may advance the positive contributory aspects and the preponderant role of the surf community in their dialogue with the decision makers. It concludes with an urgent call to recognise and accommodate different uses of the surfing reserves in developing a thorough understanding of marine-coastal environmental governance.